2009
DOI: 10.1111/j.1574-6968.2009.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the RsaL global regulator toPseudomonas aeruginosavirulence and biofilm formation

Abstract: In Pseudomonas aeruginosa, acyl-homoserine-lactone quorum sensing (acyl-HSL QS) regulates the expression of virulence factors and biofilm formation in response to cell density. The RsaL protein represses transcription of the lasI gene, encoding the 3OC(12)-HSL signal synthase. The level of 3OC(12)-HSL is 10-fold higher in an rsaL mutant than in the wild type. In this work, we studied the effect of 3OC(12)-HSL overproduction caused by the rsaL mutation by comparing the transcriptional profiles and virulence-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 30 publications
2
73
0
1
Order By: Relevance
“…The observation that the abolition of 3OC 12 -HSL production in the ppuI mutant had no significant effect on biofilm formation and pyoverdine production supports the latter hypothesis. The physiological role played by RsaL in P. putida WCS358 is similar to that observed in P. aeruginosa PAO1, since the RsaL protein of P. aeruginosa was also shown to have a positive effect on biofilm formation and to repress the production of secreted secondary metabolites (31). In contrast, the lack of an effect of the ppuI mutation on the biofilm phenotype was surprising, since previous studies with P. putida strains IsoF and PCL1445 showed that this mutation causes a significant alteration in biofilm production (3,11,35).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The observation that the abolition of 3OC 12 -HSL production in the ppuI mutant had no significant effect on biofilm formation and pyoverdine production supports the latter hypothesis. The physiological role played by RsaL in P. putida WCS358 is similar to that observed in P. aeruginosa PAO1, since the RsaL protein of P. aeruginosa was also shown to have a positive effect on biofilm formation and to repress the production of secreted secondary metabolites (31). In contrast, the lack of an effect of the ppuI mutation on the biofilm phenotype was surprising, since previous studies with P. putida strains IsoF and PCL1445 showed that this mutation causes a significant alteration in biofilm production (3,11,35).…”
Section: Discussionmentioning
confidence: 56%
“…In all these bacteria, RsaL represses the expression of the signal synthase gene and (with the sole exception of P. fuscovaginae) causes a decrease in signal molecule production. However, the RsaL protein has been investigated at the physiological and molecular levels only in P. aeruginosa PAO1 (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rampioni et al (2007) demonstrated that while RsaL and LasR are capable of binding simultaneously to the intergenic region; repression by RsaL supersedes LasR-mediated activation (Rampioni, 2007). RsaL appears to be a global regulator, controlling ~130 genes independent of its effect on lasI expression (Rampioni, 2007), including genes whose products are involved in antibiotic resistance and biofilm formation in P. aeruginosa (Rampioni, 2009). Evidence for rsaL upregulation was found in P. aeruginosa RNA harvested from sputum samples obtained from chronically infected CF patients, suggesting that RsaL plays a role in C12-HSL homeostatic control during chronic infection (Son, 2007).…”
Section: Regulators Of Qs Homeostasismentioning
confidence: 99%
“…RsaL also appears to be important in regulating the transition from planktonic to a sessile state as rsaL mutants exhibit increased swarming motility and fail to form biofilms (636).…”
Section: Qs Regulationmentioning
confidence: 99%